Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18276/ab.2018.25-06
|View full text |Cite
|
Sign up to set email alerts
|

Prey abundance supporting unusual water mite (Acari: Hydrachnidia) community in a sublacustrine spring and tributary river

Abstract: Water mites are predators on microcrustations (Copepoda, Cladocera, Ostracoda) and insect larvae (mostly Diptera). Their communities usually have great diversity with high species richness but relatively low abundance. This may have important implications for poorly investigated predator-prey interactions of water mites in natural habitats. A sublacustrine karst spring Torak and the mouth of its tributary river Čikola were examined seasonally from August 2016 to June 2017, with the aim of determining water mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Many mites had high proportions and high species identity of DNA barcodes to multiple species of chironomids (see Figs 3 and 4). Recent studies using correlative data on water mite prey complexity demonstrated that copepod, cladoceran and chironomid densities correlated with water mite abundance and species richness [34,35]. However, this was based on correlation and not on direct observation of water mites feeding or DNA studies, the latter being unique to this present study.…”
Section: Discussionmentioning
confidence: 54%
“…Many mites had high proportions and high species identity of DNA barcodes to multiple species of chironomids (see Figs 3 and 4). Recent studies using correlative data on water mite prey complexity demonstrated that copepod, cladoceran and chironomid densities correlated with water mite abundance and species richness [34,35]. However, this was based on correlation and not on direct observation of water mites feeding or DNA studies, the latter being unique to this present study.…”
Section: Discussionmentioning
confidence: 54%
“…In addition to the hydrological and hydrogeological research of karst springs, there are also biological studies. Most frequently, communities of water mites in the larger karst springs of Mountainous Croatia and Dalmatia have been studied (Pozojević et al, 2018a;2018b;2019;2020). These works have identified new water mite species, determined species richness and population density in selected springs, and monitored environmental factors affecting them.…”
Section: Modern Spring Research In Croatiamentioning
confidence: 99%
“…These works have identified new water mite species, determined species richness and population density in selected springs, and monitored environmental factors affecting them. It is important to note that the aforementioned studies compared differences in communities between limnocrene and rheocrene karst springs (Pozojević et al, 2018a;2020).…”
Section: Modern Spring Research In Croatiamentioning
confidence: 99%